How Implementation of Industrial Work Practice Program Increases Students' Competence Skills: Analysis of the Need of Workforce? - Mispandi, Mispandi; Fahrurrozi, Muh (Universitas Negeri Surabaya, 2024)
This study aims to analyze the contribution of implementing the industrial work practice program to improve student skills and competence according to the needs of the workforce. The research used in this study uses a mixed method of qualitative and quantitative methods. The sample of this study was 5 Instructors, five field supervisors, and 25 students of Hamzanwadi University who had completed the industrial work practice program. The data collection technique used was a questionnaire by random sampling. The data analysis technique from the questionnaire was processed using descriptive analysis. The results of the study showed that the instructors of the industrial work practice program contributed to the implementation of the industrial work practice program towards improving the skills competency of Hamzanwadi University students obtained in an excellent category, namely with a percentage result of 96.31%. In addition to instructors, field supervisors also influenced the implementation of the industrial work practice program towards improving the skills competency of Hamzanwadi University students, with research results of 94.72% in the outstanding category. In addition, implementing the industrial work practice program towards improving students' skills and competency in the workforce was seen from the student responses obtained with the research instrument, with research results of 97% in the outstanding category. This result shows that implementing the industrial work practice program is conducive and can improve students' skills and competencies according to the workforce's needs.